Hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin: kinetic studies - Diwakar, Makarand M.; Deshpande, R. M.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2005)
The exchange of the Rh/Triphenylphosphine trisulfonate sodium [TPPTS] complex on to an anion exchange resin results in a stable heterogenized catalyst for the hydroformylation of alkenes. The kinetics of hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin to Amberlite IRA-93 has been investigated for the first time. The rate of the reaction was found to be dependent on the partial pressure of hydrogen and 1-hexene concentrations with a first order. A maximum in the rate with increasing partial pressure of carbon monoxide was observed. A rate model has been proposed which predicts the observed rate data within reasonable error. The activation energy was found to be 84.37 kJ/mol. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogenized catalyst; Hydroformylation; ion-exchange resin; kinetics; Rhodium

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst